Intracochlear Schwannoma: Diagnosis and Management - Bittencourt,Aline Gomes (2014)
Introduction  Schwannomas of the eighth cranial nerve are benign tumors that usually occur in the internal auditory canal or the cerebellopontine angle cistern. Rarely, these tumors may originate from the neural elements within the vestibule, cochlea, or semicircular canals and are called intralabyrinthine schwannomas. Intracochlear schwannomas (ICSs) represent a small percentage of these tumors, and their diagnosis is based on high-resolution magnetic resonance imaging (MRI). Objectives  To report the clinical and radiologic features and audiometric testing results of an ICS in a 48-year-old man after a 22-month follow-up period. Resumed Report  A patient with an 8-year history of persistent tinnitus in his right ear, combined with ipsilateral progressive hearing loss and aural fullness. Audiometry revealed normal hearing in the left ear and a moderate to severe sensorineural hearing loss in the right ear, with decreased speech reception threshold and word recognition score, compared with the exam performed 5 years previously. MRI showed a small intracochlear nodular lesion in the modiolus, isointense on T1 with a high contrast enhancement on T1 postgadolinium images. During the follow-up period, there were no radiologic changes on imaging studies. Thus, a wait-and-scan policy was chosen as the lesion remained stable with no considerable growth and the patient still presents with residual hearing. Conclusions  Once diagnosed, not all ICS patients require surgery. Treatment options for ICS include stereotactic radiotherapy and rescanning policy, depending on the tumor's size, evidence of the tumor's growth, degree of hearing loss, intractable vestibular symptoms, concern about the pathologic diagnosis, and the patient's other medical conditions.